2013
DOI: 10.1089/zeb.2012.0835
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Regulation of Growth- and Metabolism-Related Factors in Zebrafish

Abstract: Zebrafish (Danio rerio) have been proposed as a possible model organism for nutritional physiology. However, this potential has not yet been realized and studies on the field remain scarce. In this work, we investigated in this species the effect of a single meal as well as that of an increase in the ratio of dietary carbohydrates/proteins on the postprandial expression of several hepatic and muscle metabolism-related genes and proteins. Fish were fed once either a commercial diet (experiment 1) or one of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 79 publications
13
35
0
Order By: Relevance
“…Although few, some genes involved in glycolysis, lipogenesis and energy production pathways were enhanced: GK and FAS (by stimulus 1), G6PDH (by stimulus 2) and 6PFK-L, PK and CS genes (by stimulus 3). These data are similar to the postprandial induction of gene expression observed in rainbow trout, gilthead seabream and zebrafish, after a high carbohydrate intake (Enes et al, 2008b;Kamalam et al, 2012;Meton et al, 2004;Panserat et al, 2000;Polakof et al, 2012b;Seiliez et al, 2013), comparable to what occurs in mammals (Kersten, 2001;Pilkis and Granner, 1992;Yamada and Noguchi, 1999). Moreover, a similar short-term regulation for higher expression of GK and HK1 glycolytic enzymes was observed in rainbow trout and zebrafish fed at first-feeding with a high level (50 to 65%) of dietary carbohydrates (Fang et al, 2014;Geurden et al, 2007Geurden et al, , 2014.…”
Section: Discussionsupporting
confidence: 84%
“…Although few, some genes involved in glycolysis, lipogenesis and energy production pathways were enhanced: GK and FAS (by stimulus 1), G6PDH (by stimulus 2) and 6PFK-L, PK and CS genes (by stimulus 3). These data are similar to the postprandial induction of gene expression observed in rainbow trout, gilthead seabream and zebrafish, after a high carbohydrate intake (Enes et al, 2008b;Kamalam et al, 2012;Meton et al, 2004;Panserat et al, 2000;Polakof et al, 2012b;Seiliez et al, 2013), comparable to what occurs in mammals (Kersten, 2001;Pilkis and Granner, 1992;Yamada and Noguchi, 1999). Moreover, a similar short-term regulation for higher expression of GK and HK1 glycolytic enzymes was observed in rainbow trout and zebrafish fed at first-feeding with a high level (50 to 65%) of dietary carbohydrates (Fang et al, 2014;Geurden et al, 2007Geurden et al, , 2014.…”
Section: Discussionsupporting
confidence: 84%
“…Also, it was shown that PEPCK expression responded to insulin self-production in zebrafish, suggesting that this pathway could be regulated in a similar manner to that in mammals (Elo et al, 2007). However, some of our results were unexpected, because it has been demonstrated in different fish species that dietary carbohydrates can induce enzymes involved on glycolysis, lipogenesis and carbohydrate digestion, as occurs in mammals (Caseras et al, 2000;Geurden et al, 2007;Kersten, 2001;Panserat et al, 2001a;Panserat et al, 2000;Panserat et al, 2001b;Polakof et al, 2011;Seiliez et al, 2013). Several scenarios can be proposed to explain the overall reduction in gene expression as a result of glucose overloading in the glucose-injected group (4 dpf), but further studies are needed to confirm each suggested hypothesis: (1) intensive cellular oxidative stress as a response to excessive nutrient (glucose) uptake (Wellen and Thompson, 2010); (2) susceptibility to modulation of mRNA transcription, as demonstrated for the phospholipase A2 gene in β-cells of rat with excess glucose availability (Metz et al, 1991); and (3) repression of master genes that control key regulatory systems (Corkey and Shirihai, 2012).…”
Section: Research Articlementioning
confidence: 55%
“…In our study, using a microinjection technique, we attempted to modify the glucose content of zebrafish yolk reserves at early stages of embryogenesis in order to assess the short-term and possible long-term modifications on gene regulation. The panel of genes selected for qPCR analysis in this study has been previously validated as good molecular markers for nutritional regulation of glucose metabolism in zebrafish (Seiliez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations